2020
DOI: 10.1136/bmjqs-2019-010639
|View full text |Cite
|
Sign up to set email alerts
|

Associations of workflow disruptions in the operating room with surgical outcomes: a systematic review and narrative synthesis

Abstract: BackgroundPerformance in the operating room is an important determinant of surgical safety. Flow disruptions (FDs) represent system-related performance problems that affect the efficiency of the surgical team and have been associated with a risk to patient safety. Despite the growing evidence base on FDs, a systematic synthesis has not yet been published.ObjectiveOur aim was to identify, evaluate and summarise the evidence on relationships between intraoperative FD events and provider, surgical process and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 65 publications
0
28
0
1
Order By: Relevance
“…Surgical errors can have a devastating effect on the surgical outcome [40]. The evidence base remains inconsistent concerning the ramifications of FDs on surgical performance and outcomes [15,41]. Notwithstanding, precarious sources of errors and patient harm associated with FD need to be mitigated [13,15,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical errors can have a devastating effect on the surgical outcome [40]. The evidence base remains inconsistent concerning the ramifications of FDs on surgical performance and outcomes [15,41]. Notwithstanding, precarious sources of errors and patient harm associated with FD need to be mitigated [13,15,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence base remains inconsistent concerning the ramifications of FDs on surgical performance and outcomes [15,41]. Notwithstanding, precarious sources of errors and patient harm associated with FD need to be mitigated [13,15,42,43]. We, therefore, set out a study assessing the effects of FDs on technical performance failures.…”
Section: Discussionmentioning
confidence: 99%
“…As additional flow disruptions occur across different factors throughout the course of the surgery, the error space widens, allowing additional opportunities for errors to occur. A recent literature review exploring the effect of surgical flow disruptions found that perioperative team members spend approximately 20.5% of operating time managing flow disruptions 11 . A proactive approach to implementing safety measures may address the error space.…”
Section: The Effect Of Flow Disruptionsmentioning
confidence: 99%
“…However, several aspects threaten highquality intraoperative information exchange 18 . Surgeons perform difficult psychomotor tasks that require their full attention [20][21][22] ; at the same time, they lead the team and have to provide the information needed for team members to carry out their tasks appropriately 23,24 . Switching attention between psychomotor and communication tasks often induces additional mental load 25 , and can interrupt the surgical flow.…”
Section: Introductionmentioning
confidence: 99%
“…It was developed based on research into: the content of instructions needed to foster team situation awareness 29 ; the characteristics of the StOP? as a short step back from the operation [30][31][32] ; timing that avoids task disruptions 22,33 ; and the issue of speaking up 27 . Before the study, the procedure was tested and adapted in several operations.…”
Section: Development and Introductionmentioning
confidence: 99%